The Pharmacological Treatment of Chronic Pain: From Guidelines to Daily Clinical Practice - Gianmarco Marcianò; Cristina Vocca; Maurizio Evangelista; Caterina Palleria; Lucia Muraca; Cecilia Galati; Francesco Monea; Liberata Sportiello; Giovambattista De Sarro; Annalisa Capuano; Luca Gallelli (MDPI AG, 2023)
In agreement with the International Association for the Study of Pain, chronic pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. To date, there are several types of pain: nociceptive, neuropathic, and nociplastic. In the present narrative review, we evaluated the characteristics of the drugs used for each type of pain, according to guidelines, and their effects in people with comorbidity to reduce the development of severe adverse events.